Chronic experimental hyperoxia elevates aerobic scope: a valid method to test for physiological oxygen limitations in fish. Issue 6 (21st September 2022) - Skeeles, Michael R.; Scheuffele, Hanna; Clark, Timothy D.
Abstract: Experimental hyperoxia has been shown to enhance the maximum oxygen uptake capacity of fishes under acute conditions, potentially offering an avenue to test prominent physiological hypotheses attempting to explain impacts of climate warming on fish populations ( e.g., gill‐oxygen limitation driving declines in fish size). Such benefits of experimental hyperoxia must persist under chronic conditions if it is to provide a valid manipulation to test the relevant hypotheses, yet the long‐term benefits of experimental hyperoxia to oxygen uptake capacity have not been examined. Here, the authors measured aerobic metabolic performance of Galaxias maculatus upon acute exposure to hyperoxia (150% air saturation) and after 5 months of acclimation, at both 15°C and 20°C. Acute hyperoxia elevated aerobic scope by 74%–94% relative to normoxic controls, and an elevation of 58%–73% persisted after 5 months of hyperoxia acclimation. When hyperoxia‐acclimated fish were acutely transitioned back to normoxia, they maintained superior aerobic performance compared with normoxic controls, suggesting an acclimation of the underlying metabolic structures/processes. In demonstrating the long‐term benefits of experimental hyperoxia on the aerobic performance of a fish, the authors encourage the use of such approaches to disentangle the role of oxygen in driving the responses of fish populations to climate warming.